Transformational agriculture Across the Mzab Valley1926-1929 - ibrir, teher; benadi, mohamed el taher (Journal of Social Sciences and Humanities, 2023)
The Mizab Valley news Paper is the Sheikh Ibrahim Abu El alyaqzan news Paper That appeared in distinct circumstances in Alegria, hère the développements of the national movement accelerated between the two wars - the period of their publication - they are considered alone in the reformist magazines that deal with the economy as they dealt with religious, social, cultural, educational and other issues. In addition to his treatment of national politics issues such as the Association of Muslim Scholars and the Algerian Islamic Conference on the one hand, and on the other hand his interest in the issue of naturalization and proselytism and everything related to the methods of French politics. Because of the press experience gained by Sheikh Abi Al-Yakdan, the newspaper faced two fronts, the first being supporting the national movement, and the second opposing French colonialism in Algeria, denouncing it and warning against it